1961
DOI: 10.1002/jsfa.2740120508
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of meats with ionising radiations. VI.—changes in quality during storage of sterilised raw beef and pork

Abstract: Radiation‐sterilised raw beef and pork were stored at temperatures from −20° to + 37°, and changes in appearance, odour, texture and flavour, during several months, were assessed by a panel using ranking and hedonic scores. The changes in appearance were deleterious, but of minor importance save at the highest temperatures. There was a softening of texture and loss of fluid, presumed due to autolytic changes, also greater at the higher temperatures; but, even after several months at 37°, the fibrous texture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1961
1961
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The main factor in survival of Staphylococcus, Streptococcus, Luctobacillus, and Bacillus in cheese exposed to 40 kGy irradiation probably was the use of sub-freezing temperatures during the irradiation treatment, resulting in a decreased number of secondary radical reactions involving the bacteria (Urbain, 1986) and increased radiation resistance of the microorganisms. Coleby et al (1961) reported that 50 kGy were necessary for radiation sterilization at -75°C of endogenous organisms in meat, which was in the range of the approximate sterilization doses we found for dairy products. A few studies have reported, however, that freezing may decrease resistance, but this has mainly been shown in spores (Edwards et al, 1954).…”
Section: Effects Of Irradiation On Endogenous Microbial Populationsmentioning
confidence: 55%
See 1 more Smart Citation
“…The main factor in survival of Staphylococcus, Streptococcus, Luctobacillus, and Bacillus in cheese exposed to 40 kGy irradiation probably was the use of sub-freezing temperatures during the irradiation treatment, resulting in a decreased number of secondary radical reactions involving the bacteria (Urbain, 1986) and increased radiation resistance of the microorganisms. Coleby et al (1961) reported that 50 kGy were necessary for radiation sterilization at -75°C of endogenous organisms in meat, which was in the range of the approximate sterilization doses we found for dairy products. A few studies have reported, however, that freezing may decrease resistance, but this has mainly been shown in spores (Edwards et al, 1954).…”
Section: Effects Of Irradiation On Endogenous Microbial Populationsmentioning
confidence: 55%
“…Coleby et al (1961) reported that 50 kGy were necessary for radiation sterilization at -75°C of endogenous organisms in meat, which was in the range of the approximate sterilization doses we found for dairy products. A few studies have reported, however, that freezing may decrease resistance, but this has mainly been shown in spores (Edwards et al, 1954).…”
Section: Effects Of Irradiation On Endogenous Microbial Populationsmentioning
confidence: 76%
“…Luchsinger et al (1996b) reported discoloration and color instability for aerobically packaged pork irradiated with up to 3.85 kGy, whereas irradiated, vacuum-packaged pork was redder and more color stable. Freezing to -80C (Coleby et al 1961;Hultin 1985) or precooking to deactivate enzymes (Taub et al 1979;van Laack 1994) minimized quality changes in irradiated muscle foods. Our objective was to determine the effects of 2.0 and 3.5 kGy of nonradioactive irradiation versus no irradiation on color and oxidative stability of frozen, raw and precooked, ground beef patties with 10 and 22% fat packaged in vacuum and aerobically.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of packaging and temperature on the quality of irradiated meats are uncertain. Freezing to below -8OC (Coleby et al 1961;Hultin 1985) minimized quality changes in irradiated muscle foods. However, this approach is not practical for much of the beef industry.…”
Section: Introductionmentioning
confidence: 99%